The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2018
DOI: 10.1159/000487970
|View full text |Cite|
|
Sign up to set email alerts
|

Sestrin-Mediated Inhibition of Stress-Induced Intervertebral Disc Degradation Through the Enhancement of Autophagy

Abstract: Background/Aims: Intervertebral disc degeneration (IDD) is a pathological process that is the primary cause of low back pain and is potentially mediated by compromised stress defense. Sestrins (Sesn) promote cell survival under stress conditions and regulate AMP-activated protein kinase (AMPK) and mammalian target of rapamycin (mTOR) signaling. Here, we investigated the expression of Sesn in normal and degraded nucleus pulposus (NP) cells and its potential roles during IDD pathogenesis. Methods: Sesn expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 65 publications
0
12
0
Order By: Relevance
“…Autophagy is a non-apoptotic, programmed cell death that leads to the self-digestion and degradation of unwanted proteins and organelles to prevent cellular stress and maintain cell function (157). Cells can resist apoptosis and senescence by activating autophagy, which alleviates the progression of certain chronic degenerative diseases (158)(159)(160)(161)(162). Autophagy plays a crucial role in the pathogenesis of a number of degenerative diseases, including osteoarthritis (158) and IDD (159)(160)(161)(162).…”
Section: Potential Role Of Hif-1αmentioning
confidence: 99%
See 2 more Smart Citations
“…Autophagy is a non-apoptotic, programmed cell death that leads to the self-digestion and degradation of unwanted proteins and organelles to prevent cellular stress and maintain cell function (157). Cells can resist apoptosis and senescence by activating autophagy, which alleviates the progression of certain chronic degenerative diseases (158)(159)(160)(161)(162). Autophagy plays a crucial role in the pathogenesis of a number of degenerative diseases, including osteoarthritis (158) and IDD (159)(160)(161)(162).…”
Section: Potential Role Of Hif-1αmentioning
confidence: 99%
“…Cells can resist apoptosis and senescence by activating autophagy, which alleviates the progression of certain chronic degenerative diseases (158)(159)(160)(161)(162). Autophagy plays a crucial role in the pathogenesis of a number of degenerative diseases, including osteoarthritis (158) and IDD (159)(160)(161)(162). The autophagy-related genes or proteins beclin 1, cathepsin B, damage-regulated autophagy modulator 1 and p65 were highly expressed in degenerated IVD tissues compared with normal, healthy IVD tissues (163).…”
Section: Potential Role Of Hif-1αmentioning
confidence: 99%
See 1 more Smart Citation
“…However, Sesn3 is somewhat redundant to Sesn2 in metabolic function and autophagy induction in liver and colon tissues (Lee et al, 2012;Ro et al, 2016). Although ectopically expressed Sestrin2 protein is mostly found in cytoplasm (Parmigiani et al, 2014), recent studies suggest that Sestrin2 is associated with mitochondria (Kim H. et al, 2020;Kovaleva et al, 2020), nucleus (Tu et al, 2018;Wang L.X. et al, 2020), and endoplasmic reticulum (ER) (Wang L.X.…”
Section: Introduction Of Sestrinsmentioning
confidence: 99%
“…Autophagy, the process of non-apoptotic, programmed cell death, is a physiological response to hypoxia and exhibits a complicated association with hypoxia [ 98 , 99 ]. The level of autophagy changes according to IVD degeneration and age [ 98 , 100 ]. It has been shown that NP cells show higher autophagy activity under normoxia than under hypoxia [ 98 , 101 ].…”
Section: Regeneration For Ivd Degeneration—focused On Hif-1αmentioning
confidence: 99%